Assessing the Prevalence’s of Fascioliasis in Goats in the Central Areas of Khost Province Afghanistan - Mumtaz, Ibrahimi; Khalid, Basharmal; Mirafzal, Afzali (Journal for Research in Applied Sciences and Biotechnology, 2024)
Fascioliasis is an important parasitic disease of domestic animals, which causes weakness, loss of appetite, reduced production and death of animals in domestic animals, which causes more financial losses to farmers. this study aims to investigate and determine the prevalence’s of fascioliasis in goats in the central areas of Khost province. the data were analyzed using SPSS with chi square test. A total 100 goats were investigated and the positive prevalence rate of the fascioliasis was 38%. In this study, the age and sex of the animals were also considered. the prevalence rate based on age was 40% in young goat and 37.1% in adult goats. According to sex, the prevalence of fascioliasis in male goats was 42.8% and in female goats was 35.3%. the positive incidence of the fascioliasis was higher in male animals than in female goats based on sex. and based on age the positive incidence was higher in young goats than in adult goats. also, the prevalence of fascioliasis in young male was 50%, but in young female goats the prevalence of fascioliasis was 35%. 40% in adult male and 35.5% in adult female goats detected.